Persistent high-growth firms in China's manufacturing - Daniele Moschella; Federico Tamagni; Xiaodan Yu (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
This article investigates the characteristics of high-growth (HG) firms in Chinese manufacturing, and further explores the effects of firm characteristics on persistence of high-growth. We employ a multidimensional definition of HG firms that simultaneously accounts for growth of sales and employment. Exploiting a representative panel covering the period of the China's miracle, we find that HG firms outperform other firms, showing higher productivity, higher profitability, larger investment intensity, higher sales from product innovation, lower interest expenses and lower leverage. HG firms are also relatively young, larger in size, more often exporters and more concentrated in non-State-controlled companies. However, regression analysis suggests that none of the indicators of structural characteristics and performance considered above displays any statistical association with the ability to persistently replicate high-growth over time. The results speak against the long-run effectiveness of policies supporting the creation and backing of high-growth firms.
Keywords: D22; D24; L26; 330; Entrepreneurship; Firm growth; High-growth firms; Persistent high-growth firms